A cautionary note on elasticity analyses in a ternary plot using randomly generated population matrices. Issue 1 (23rd May 2018) - Takada, Takenori; Kawai, Yuka; Salguero‐Gómez, Roberto
Abstract: Matrix population models are one of the most common mathematical models in ecology, which describe the dynamics of stage‐structured populations and provide us many population statistics. One of the statistics, elasticity onto population growth rate, is frequently used and represents the degree of the relative impact of life history parameters to the population growth rate. Due to the utility of elasticities for cross‐taxonomic comparisons, Silvertown and his coauthors have published multiple papers and reported the relationship between elasticities and life forms (or life history) in multiple plant species, using a triangle map (called "ternary plot"). To understand why their elasticities are located in specific regions of the ternary plot, we constructed four archetypes of population matrices, from which we simulated 24, 000 randomly generated population matrices and obtained the consequent elasticities. We found a large discrepancy when comparing our results to those in Silvertown et al.'s study (Conserv Biol 10:591–597, 1996): for our simulated matrices where rapid transitions were not allowed (e.g., trees), the elasticity distribution resulted in a line across the ternary plot. We provided the mathematical proof for this result, and found that its slope depends on matrix dimension. We also used 1230 matrices from the COMPADRE Plant Matrix Database and calculated the elasticities. Our simulated results were validated with field data from COMPADRE: two straight lines appeared in the ternary plot. Furthermore, we answered several addressed questions, such as, "Is there any special elasticity distribution in matrices with high population growth rates?" and "Why are the elasticities of natural populations concentrated in the upper half of the ternary plot?".